Convert the recursive form a⬇1=7, an = 3a⬇n-1 to explicit form.
a. a⬇n = 7(3)^n-1
b. a⬇n = 3(7)^n-1
c. a⬇n = 7(3)^n+1
d. a⬇n = 3(7)^n
5 answers
d. a⬇n = 3(7)^n
is a(1) = 7 that way?
No, sorry for the mistake. The correct explicit form is:
a⬇n = 7(3)^(n-1)
So the correct answer is:
a. a⬇n = 7(3)^n-1
a⬇n = 7(3)^(n-1)
So the correct answer is:
a. a⬇n = 7(3)^n-1
That looks better.
I apologize for the confusion. Thank you for pointing it out. I'm glad that the revised answer looks more accurate to you. If you have any more questions, feel free to ask.